2019
DOI: 10.1111/1440-1703.12035
|View full text |Cite
|
Sign up to set email alerts
|

Invasive moth facilitates use of a native food plant by other native and invasive arthropods

Abstract: Organisms that invade new habitats exploit new resources or niches and influence native species. Here, we examine how an invasive moth, the parsnip webworm (Depressaria radiella, formerly D. pastinacella), facilitates interactions with other arthropods in spatially separated populations of native cow parsnip (Heracleum maximum) in the Rocky Mountains (New Mexico and Colorado). We compare this with results on small hogweed (Heracleum sphondylium) in the Netherlands, where both the plant and herbivore are native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…In line with previous studies (i.e. Harvey et al, 2016;Harvey et al, 2019), stems of plants at site 3 that were naturally perforated by D. radiella caterpillars also contained woodlice and earwigs in numbers similar to those found in stems with artificially perforated holes. Species composition of the arthropod community within hogweed stems and in the vegetation surrounding the stems differed;…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with previous studies (i.e. Harvey et al, 2016;Harvey et al, 2019), stems of plants at site 3 that were naturally perforated by D. radiella caterpillars also contained woodlice and earwigs in numbers similar to those found in stems with artificially perforated holes. Species composition of the arthropod community within hogweed stems and in the vegetation surrounding the stems differed;…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, both P. scaber and F. auricularia were also introduced into North America and are now widely distributed. A previous study conducted in the Rocky Mountains of Colorado and New Mexico found that native populations of the cow parsnip, H. maximum , that had been infested with D. radiella larvae also harboured variable numbers of earwigs (but not woodlice) that similarly entered the stems through the holes chewed by mature webworm caterpillars Harvey et al (2019). Remarkably, the authors even found a native North American Clubiona species inside several D. radiella ‐perforated stems of cow parsnip H. maxima plants.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One of the major differences between native (European) and invasive (North American) interactions between webworms and their food plants is that populations of hogweeds and wild parsnips in the native European range have been constantly exposed to threat of webworm attack for millennia. In contrast, in the United States, where webworms are invasive, they attack the native cow parsnip (Harvey et al 2019) or invasive populations of wild parsnip (Lohman et al 1996). Cow parsnips do not have a long co-evolutionary history with webworms, whereas wild parsnips were re-acquainted with webworms after at least several decades of isolation from them.…”
Section: Discussionmentioning
confidence: 99%